Microsoft Encarta interactive world atlas 2001 - Microsoft Corporation; Microsoft Corporation (Redmond, Wash. Microsoft Corp., 2000)
Offers 1.8 million place names plus in-depth country articles with unique cultural information. Users can choose from more than 21 different maps styles, add or remove place names, borders, and topographic detail to create custom maps for reports and presentations.
disc 1: Interactive world atlas -- [disc 2]: Installation & resources.
System requirements: Multimedia PC with a Pentium 90 or higher processor; Microsoft Windows 95, or Windows 98 or later operating system, or Windows NT workstation operating system version 4.0 or later with Service Pack 3 or later; 24 MB of RAM for Windows 95 or Windows 98; 32 MB for Windows NT Workstation; 75 MB of available hard-disk space (25 MB additional needed for install); Quad-speed or faster CD-ROM drive; Super VGA, 256-color or higher monitor supporting 640 X 480 or higher resolution with 16-bit color recommended; Local bus video with 1 MB or more of video memory; Microsoft Mouse, Microsoft IntelliMouse or compatible pointing device; 16-bit sound card with speakers or headphones.
Keywords: Atlases; Geography -- Maps